Student Debt in the United States: Rhetoric vs Reality - Baum, Sandy (International Higher Education, 2018)
The general notion of a student debt “crisis” in the United States is rooted in misperceptions. The problems lie largely with students who leave school without a credential, with those who attend for-profit institutions, and with older adults returning to school—not with young, four-year college graduates.